Mechanistic Understanding of Size‐Dependent Oxygen Reduction Activity and Selectivity over Pt/CNT Nanocatalysts. Issue 27 (21st March 2019) - Gan, Jie; Luo, Wei; Chen, Wenyao; Guo, Jianing; Xiang, Zhonghua; Chen, Bingxu; Yang, Fan; Cao, Yunjun; Song, Fei; Duan, Xuezhi; Zhou, Xinggui
Abstract : Identifying the underlying nature of the structure sensitivity of oxygen reduction reaction (ORR) over carbon supported Pt catalysts is an important but challenging issue in electrochemical system. In this work, we combine experiments, density functional theory calculations with model calculations to clarify the size‐dependent ORR activity and selectivity over differently sized Pt/CNT catalysts. HAADF‐STEM, HRTEM and XPS measurements show that the Pt nanoparticles supported on CNT possess a well‐defined truncated octahedron shape in most cases and similar electronic properties. The observed size‐insensitive TOFactive site based on the number of Pt(111) atoms suggests the Pt(111) surface as the dominant active site. Moreover, the Pt(111) surface is also suggested as the dominant active sites for the formation of H2 O2, and the catalyst with the higher Pt binding energy facilitates the oxygen reduction to H2 O. The insights revealed here could shed new light on the design and optimization of Pt‐based ORR catalysts. Abstract : The size‐dependent ORR activity and selectivity over Pt/CNT catalysts have been clarified by combining the experiments, DFT calculations and model calculations. The Pt(111) surface, especially for the catalyst with the higher Pt binding energy, is favourable for the oxygen reduction to H2 O.